A review of the economic and ecological constraints on animal draft cultivation in sub-Saharan Africa - Ehui, Simeon K.; Polson, R. (Elsevier, 1993)
With a limited number of cash cropping areas, sub-Saharan Africa has the lowest level of mechanization including animal-driven implements and use of tractors. In this paper previous research is reviewed to evaluate the economic and ecological constraints to animal draft cultivation. Results of past studies have shown that the animal-drawn plow is only profitable at higher intensities of farming induced by population growth and better market access. Utilization and use of animal-drawn implements will, however, be low in areas characterized by light soils (arid zones) or areas prone to erosion, or with a short growing season. Other constraints on the profitable use of animal draft are farmers' characteristics and policy factors. Farm and family size, the farmer's experience and types of equipment are shown to play important roles. One factor often ignored is the opportunity cost of labour and capital during off-farm activities. Utilization of animal traction implies tending costs. If, however, the cost of maintaining the animal outside the peak season reduced off-farm income opportunities, farmers are not likely to make a profitable use of the plow. Other opportunities available to the farmer (eg. beef production when beef prices are high) are likely to have a negative impact on utilization of oxen cultivation. Rural-urban dualism which characterizes African agriculture owing to low agricultural productivity and high wages in cities, is likely to be an important constraint.